Austerity and the household: The politics of economic storytelling. Issue 4 (December 2016) - Montgomerie, Johnna
Abstract Austerity is a key organising concept governing the British political economy since the 2008 financial crisis, it is our present with a future that is still unfolding. As such the outcomes of Austerity are not yet fully known. As such, this paper argues that Austerity is an experiment in economic storytelling that seeks to cope with the post-crash British economy by trying to revive and consolidate the Anglo-American financialised growth model, and, by doing so, actively prevents the necessary structural economic reforms needed to achieve the desired revitalising of the economy. The first section brings into dialogue the structural accounts that explainwhy Austerity is the outcome of the 2008 financial crisis with the everyday understandings ofhow Austerity is made through processes by forging common-sense narratives of economic crisis. These accounts are refracted through a feminist political economy lens that is attuned to the dynamics of power – orwho must pay the costs of Austerity. The second section details 'the debt story' in terms of what is told, but also untold, about the UK's alleged debt crisis. The next section focuses on the household to make visible how Austerity crafts political states of intervention and exception that directly inhibit economic change or reform of financialisation. Finally, the paper concludes by considering what feminist-inspired analysis of household can reveal about the fundamental flaws of financialisation under the auspices of Austerity – that debts are both public and private at the same time, transforming the household sector into the ultimate guarantor of continued financialised expansion.